Does the Degree of Trunk Bending Predict Patient Disability, Motor Impairment, Falls, and Back Pain in Parkinson's Disease? - Geroin, Christian; Artusi, Carlo Alberto; Gandolfi, Marialuisa; Zanolin, Elisabetta; Ceravolo, Roberto; Capecci, Marianna; Andrenelli, Elisa; Ceravolo, Maria Gabriella; Bonanni, Laura; Onofrj, Marco; Telese, Roberta; Bellavita, Giulia; et al. (Frontiers in Neurology, 2020)
BACKGROUND: Postural abnormalities in Parkinson’s disease(PD) form a spectrum of functional trunk misalignment, ranging from a “typical” parkinsonian stooped posture to progressively greater degrees of spine deviation. OBJECTIVE: To analyze the association between degree of postural abnormalities and disability and to determine cut-off values of trunk bending associated with limitations in activities of daily living(ADLs), motor impairment, falls, and back pain. METHODS: The study population was 283 PD patients with ≥5° of forward trunk bending (FTB), lateral trunk bending (LTB) or forward neck bending (FNB). The degrees were calculated using a wall goniometer (WG) and software-based measurements (SBM). Logistic regression models were used to identify the degree of bending associated with moderate/severe limitation in ADLs (Movement Disorders Society Unified PD Rating Scale [MDS-UPDRS] part II ≥ 17), moderate/severe motor impairment (MDS-UPDRS part III ≥ 33), history of falls (≥ 1), and moderate/severe back pain intensity (numeric rating scale ≥ 4). The optimal cut-off was identified using receiver operating characteristic (ROC) curves. RESULTS: We found significant associations between modified Hoehn&Yahr stage, disease duration, and sex and limitation in ADLs, motor impairment, back pain intensity, and history of falls. Degree of trunk bending was associated only with motor impairment in LTB (odds ratio [OR] 1.12; 95% confidence interval [CI], 1.03-1.22). ROC curves showed that patients with LTB of 10.5° (SBM, AUC 0.626) may have moderate/severe motor impairment. CONCLUSIONS: The severity of trunk misalignment does not fully explain limitation in ADLs, motor impairment, falls, and back pain. Multiple factors possibly related to an aggressive PD phenotype may account for disability in PD patients with FTB, LTB, and FNB.